Maqasid Al-Syariah Mendorong Keadilan Dan Keseimbangan Dalam Hukum Islam - Sumarta, Sumarta; Burhanudin, Burhandin; Budiyanto, Tenda (LPPM IAI Pangeran Dharma Kusuma Segeran Indramayu, 2024)
In the context of Maqasid Al-Syariah, justice and balance are considered as the fundamental pillars in the formation and implementation of Islamic law. This helps prevent the misuse of the law and ensures that it aligns with Islamic values that promote peace, justice, and social welfare. Maqasid Al-Syariah is a key concept in Islamic law that advocates for justice and balance. By adhering to these principles, Islamic law strives to achieve broader objectives such as safeguarding individual rights, promoting societal well-being, and maintaining a balanced relationship with God. Therefore, Maqasid Al-Syariah plays a crucial role in shaping a fair and equitable Islamic legal system. Keywords: Islamic Law, Justice and Balance